Pengaruh Penerapan Model Pembelajaran REACT terhadap Hasil Belajar Siswa Kelas 6 SD Negeri 10 Sungai Sapih Kuranji - Kintan Fitriani; Ulfia Rahmi (EDUTECH, 2022)
The research is based on the problem that the researcher found in grade 6 of SDN 10 Sungai Sapih Padang where student learning outcomes are very low in PKN subjects in the material of socio-cultural and economic diversity due to various factors. The researcher decided to implement the REACT learning model in order to improve the learning outcomes of students in the 6th grade.This study is a quasi-experimental study with class 6B as the experimental class and class 6C as the control class. The procedure is preparation, research and assessment. The technique of collecting data in this research is a test in the form of objective questions, as well as documentation with the instrument, namely test items. The tests used are normality, homogeneity and independent.Based on the analysis, it was found that there were differences in learning outcomes between classes taught with the REACT and conventional models in PKN subjects on socio-cultural and economic diversity. with the difference in the final score, namely in the experimental class the average value is 82, the highest score is 100 and the lowest is 50, while the control class has an average value of 7, the highest score is 90 and the lowest is 55. So it can be seen if there is a significant difference which can also be seen from the test results. the hypothesis obtained 0.05 (Sig. 0.000 0.05) means that Ha is accepted. The conclusion is that there are differences in the learning outcomes of students who study with the REACT learning model and students who study conventionally on PKN subjects in the socio-cultural and economic diversity of SDN 10 Sungai Sapih Kuranji.